(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Queer theories emerge from postmodern nominalist constructivism under the assumption that all things are discursive fictions, all ontology, a substantialist and dualistic narrative, and there is nothing real outside of socio-linguistic constructions and deconstructions. In the case of sexual difference, queer theories assimilate it to the hetero-normative signifiers of the old bio-political regime, and consequently abolished it by means of an ideological operative that brings us today to a post-feminism without women, where the speaking subjects arbitrarily techno-produce their bodies and sexualities. Assuming some philosophical assumptions of new material realisms, the present article aims at making visible the hidden essentialism of postmodern constructivism, its barely disguised femino-phobia and the effective violence—symbolic and non-symbolic— that it implies for actual women, and feminist agenda.